Economic Assessment of the Level of Safety in the Railway Transport on a Base an Arised Emergency Situations - Razmov, Todor; Varadinova, Julia (Research Papers, 2021)
A methodology for economic assessment of the level of railway safety on the basis of the emerged emergencies has been presented. The level of safety is a basic indicator of the normal operation of the railway network. For quantitative and economic evaluation on the safety requires an appropriate quantitative meter and its corresponding unit cost. The number of accidents attributed to the total amount of trains work performed per year was selected as the main indicator. To determine its unit value, an analysis was made of the costs associated with taking into account the negative effects of emergency interruptions on the operation of the railway network and the costs associated with eliminating the consequences of an emergency. The impact of accidents, which also include incidents and irregularities, on the operation and trains work depends on the capacity and reserve capacity of the railway network. Summarized, publicly available and aggregated data were used to determine them. An option is also presented in which scheduled traffic interruptions are set in advance in the train movement schedule. The unit cost is determined on the basis of the following components: cost of eliminating the consequences of the accident, additional operational costs of delays related to the trains detention and the subsequent normalization of traffic and cost of cancelled trains.